Uitdagings vir die Afrikaanse Historikus (Historia, 2021)
Challenges to the Afrikaans historian. The Afrikaans historian is faced with important challenges today. This is clear from the serious criticism of his historical writings, conduct and attitudes. Two of the most central points of criticism are his inability to acquaint himself sufficiently with the latest trends in international historiography, and his biased focus only on the white man's role in South African history. The Afrikaans historian is to a large extent still loyal to the Rankean tradition which dates back to the 19th century. As a result of this he places too much emphasis on mere political events. Important history-making processes, such as social and economic factors, do not receive sufficient attention. On the other hand, English speaking historians in South Africa have, because of their strong language, cultural and academic ties abroad, been more aware of new trends in their historical writings. During the last few years some Afrikaans historians have been reacting positively to this by having in-depth discussions about the situation. This does not mean that the Afrikaans historian has to follow slavishly everything coming from abroad, nor that he should, sacrifice the autonomous character of his discipline. However, dialogue and debate bring clarity and reassessment of aims and principles. Afrikaans historiography is also accused of bias in favour of the whites, and of not doing justice to the role of people of colour in South African history. The history of the whites can only be properly understood within the context of the history of all the peoples of South Africa.Geskiedskrywing word reeds vir duisende jare bedryf. Tog is Geskiedenis as 'n selfstandige akademiese dissipline eers teen die begin van die 19de eeu gevestig. Hierin het die Duitse historici Barthold Niebuhr (1776-1831) en veral Leopold von Ranke (1795-1886) 'n leidende rol gespeel. Vir baie lank het die Rankeaanse tradisie wat hieruit voortgespruit het, die geskiedskrywing oorheers. Die skool se hermeneuties-individualiserende benadering met sterk klem op hoofsaaklik politieke gebeurtenisse, het egter in die loop van die 19de eeu verwydering gebring tussen die geskiedeniswetenskap en die sosiale wetenskappe met hul meer generaliserende benadering. Eers teen die einde van die 19de eeu en in die loop van die 20ste eeu het 'n lewendige debat ontstaan oor vernuwing in die geskiedeniswetenskap en die rol wat sosiale wetenskappe hierin moet speel. Dit het 'n verryking en verbreding van die geskiedeniswetenskap tot gevolg gehad. So byvoorbeeld het die Annalesskool in Frankryk, met sy sogenaamde strukturele benadering, soveel opgang gemaak dat dit tans groot prominensie geniet. Die vernuwingsbeweging het ook in ander Westerse lande neerslag gevind. Suid-Afrika, en veral Afrikaanse historici, is nie in dieselfde mate hierdeur beinvloed nie. Dit bied dus 'n besondere uitdaging vir die Afrikaanse historikus van vandag. Daarbenewens moet Suid- Afrikaanse geskiedskrywing ook reg laat geskied aan ons land se plurale samelewing.
Keywords: Bias; Bevooroordeel; Historiografie; Historiography; History; Geskiedenis; Historia; Afrikaans Historian; Afrikaanse Historikus; 19de eeu; 19th century; 20ste eeu; 20th century